Confession and Hope: Ekklesia’s Task in the Global Emergency - Timothy Gorringe (Religions, 2020)
Humanity is currently faced with deadly dangers that could bring about the breakdown of civilization, and even the end of human life on earth in short order. The Marxist and Green thinker Rudolf Bahro spoke of a ‘logic of salvation’, which involved a return to the idea of God. Ekklesia arose as a witness to such a logic of salvation. It can be understood as a social movement, that sketches out a prefigurative politics that can then be realised. The contemporary church needs to recover this understanding, adopting climate change as a confessional issue that defines its common life. This could be part of a practical logic of salvation.